Determinan Minat Investasi Bagi Mahasiswa di Kota Solo - Maharani Suprihatin; Ari Susanti (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to determine the effect of investment knowledge, information technology, perceived return and perceived risk on investment interest among students in Solo. This research was carried out in the city of Solo, with active students studying in the city of Solo as the target population. This study uses primary data whose population is not known with certainty, so the calculation uses the Roscoe formula (1986) and a minimum sample of 107 respondents is found. This study obtained the results of multiple linear regression analysis and hypothesis testing, processed with SPSS 25. Partially, information technology, investment knowledge and risk perception have a negative and insignificant effect on students' investment interest. Partially, perceived return has a positive and significant effect on students' investment interest. Simultaneously, information technology, investment knowledge, perceived return and perceived risk affect students' investment interest in Solo City.